READING THE TEACHER’S LANGUAGE: AN ANALYSIS OF VERBAL AND NONVERBAL COMMUNICATION EFFECTS ON CLASSROOM INTERACTION IN HIGHER EDUCATION - Sry Wahyuni; Isnaeni Isnaeni (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study explores students’ perceptions of teachers’ verbal and nonverbal communication and how these communication behaviors influence classroom interaction and learning outcomes. Using a qualitative descriptive approach, observation and interview were used to gained the data. Two foreign language lecturers from Universitas Negeri Makassar were chosen as the sample of this research. The findings show that effective classroom interaction emerges from the combination of verbal and nonverbal communication rather than from a single medium of communication. Finding revealed that various forms of teacher behavior, such as explaining material with hand gestures, giving directions supported by gestures, smiling while asking questions, maintaining appropriate personal distance, and offering praise accompanied by positive facial expressions, significantly enhanced their learning experience. These combination of verbal and nonverbal communication helped students understand explanations more easily, encouraged them to speak, increased their enjoyment of the learning process, and boosting their spirit. Overall, this study demonstrates that meaningful classroom interaction is shaped by the teacher’s ability to integrate verbal explanations with effective nonverbal communication, highlighting the importance of communication awareness and training for teachers in higher education.